2002
DOI: 10.1093/cercor/12.10.1024
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Reelin and Cajal-Retzius Cells in the Developmental Formation of Vertical Columnar Structures in the Cerebral Cortex: Evidence from the Study of Mouse Presubicular Cortex

Abstract: The mammalian cerebral cortex is organized into horizontal and vertical arrays of neurons and their fiber connections that form anatomically and physiologically distinct laminar and columnar compartments. However, the developmental mechanism(s) underlying this dichotomous pattern remains a mystery. We provide anatomical evidence suggesting that reelin, a diffusible protein produced and secreted by Cajal-Retzius cells, is involved in the developmental formation of the vertical cell structures in the mouse presu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…Because the manipulation of the serotonergic system altered brain reelin levels, it also could have an effect on the late embryonic stages of cortical laminar and columnar development, which depend on Cajal-Retzius cells and their transient networks (Marín-Padilla, 1998;Nishikawa et al, 2002;Luhmann et al, 2003). To see if supragranular cortical layers were affected in young pups (postnatal day 7) exposed to 5-MT before birth, we analyzed their presubicular cortex, which has visible supragranular columns in early postnatal life (Van Groen and Wyss, 1990;Nishikawa et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the manipulation of the serotonergic system altered brain reelin levels, it also could have an effect on the late embryonic stages of cortical laminar and columnar development, which depend on Cajal-Retzius cells and their transient networks (Marín-Padilla, 1998;Nishikawa et al, 2002;Luhmann et al, 2003). To see if supragranular cortical layers were affected in young pups (postnatal day 7) exposed to 5-MT before birth, we analyzed their presubicular cortex, which has visible supragranular columns in early postnatal life (Van Groen and Wyss, 1990;Nishikawa et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it has been proposed that they may form contacts with Cajal-Retzius (CR) cells (Radnikow et al, 2002), but no actual synaptic contacts have so far been demonstrated. CR cells are located in the MZ and are considered to be necessary for the correct positioning of neurons in cortical layers (Ogawa et al, 1995;Marín-Padilla, 1998;Dulabon et al, 2000;Hack et al, 2002;Ang et al, 2003;Rakic and Zecevic, 2003), as well as in radial columns (Nishikawa et al, 2002;Luhmann et al, 2003). Because microcolumns are basic anatomical and functional units of the cerebral cortex (Jones, 2000;Buxhoeveden and Casanova, 2002), their abnormalities underlie several neurological disorders in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Both serotonin and Cajal-Retzius cells have been implicated in the formation of cortical columns (16,17). Nishikawa et al (16) postulated that reelin regulation of early postnatal maturation of dendritic arborization is involved in the development of vertical columnar structures in the mouse presubicular cortex. They hypothesized that reelin may act as a stop signal for growth and branching of apical dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, in addition to their role in migration and positioning of postmitotic neurons, reelin-secreting neurons are also involved in the formation of vertical cortical columns. For example, the reeler mouse, an autosomal recessive mutant in which reelin is defective, displays abnormalities in presubicular columns, which led Nishikawa et al (16) to postulate that reelin may act as a stop signal for dendritic extensions of cortical neurons. In addition, Janusonis et al (17) showed that serotonergic input on Cajal-Retzius cells is important for proper corticogenesis, as disruption of the serotonergic system during embryonic development results in lower levels of whole-brain reelin and a disturbed formation of cortical columns in the presubicular cortex.…”
Section: -Ht3 Receptor ͉ Cajal-retzius Cells ͉ Postnatal Developmentmentioning
confidence: 99%
“…32 Reelin is a key molecule during corticogenesis, guiding the migration and positioning of proliferating neurons, and influencing cortical lamination, columnarity, and synaptic connectivity. [33][34][35][36] During development, reelin is secreted by Cajal-Retzius cells in the marginal zone. [37][38][39] It is a serine protease, 40 and acts upon neurons, and maybe glia, 41 via several receptor-mediated mechanisms.…”
mentioning
confidence: 99%